THE DISCOURSE OF SEX AND MARRIAGE IN THE NOVEL THE CURSE OF BEAUTY BY INDAH HANACO - Farokhah, Fiqih Aisyatul (UIN Sunan Kudus, 2019)
Sex since the beginning of the day is now no better in civilization. Not only that, human life cannot be avoided by sex and sexuality. Even so, high-quality sex and sexuality itself have different interpretations in every hour of culture. Some say that sex is taboo and not worthy of discussion in the general public, some who view sex as a fundamental part of humans. This can be seen through how the State has intervened in matters of the body, especially sexuality. Likewise with women who work as SPG who have never been separated from sex and sexuality. Their sex lives are always in the spotlight for the public, moreover, they are not like other women who crave life in a marriage institution as their life's purpose in curbing their sexuality. This article attempts to show; What is the meaning of the sexuality discourse depicted in the beautiful novel of The Curse of Beauty by Hanaco? How beautiful is Hanaco interpreting the concept of sexuality through a sexuality discourse built on the novel The Curse of Beauty? And what are the thoughts of the author on the sexuality discourse formed as sexual control through the marriage discourse of women who work as Sales Promotion Girl (SPG) represented in the novel The Curse of Beauty? The research is focused on analyzing the representation of the sexuality of SPG in the novel “The Curse of Beauty”. The design of the research is descriptive qualitative. Data are taken from all descriptive concerning SPG body appearance to understand the narrative meaning of the body. It applies Foucault’s discourse theory.